An eigenvalue control charting for process variability monitoring - Noor, A. M. (2011)
This paper proposes a control charting of each eigenvalue of sample covariance matrix to monitor the shift in multivariate process variability. Its performance will be compared with sample generalized variance chart, the most widely used control charting in practice. A case study using a real industrial problem shows that both charts are complementary. They might give different signal.